2023
DOI: 10.1332/239868021x16430290579843
|View full text |Cite
|
Sign up to set email alerts
|

Partner-violent and non-violent fathers’ descriptions of co-parenting

Abstract: We examined how men in treatment for intimate partner violence and non-violent men described the mother of their child, and their co-parenting. We interviewed six cohabiting and five non-cohabiting fathers in treatment for intimate partner violence (IPV), and six non-violent fathers on their everyday-life experience of being a father. We performed a theory driven thematic analysis, using ‘we-ness’ as an organising concept. In contrast to non-violent fathers, partner-violent fathers’ descriptions of the co-pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Small scale studies in Canada and Norway have compared documented IPV perpetrators with non‐perpetrators and found clear differences in abusive men's perceptions of mothers and of the coparenting relationship (Mohaupt & Duckert, 2022; Thompson‐Walsh et al, 2018). For example, Mohaupt and Duckert (2022) found abusive men's descriptions of coparenting lacked reference to mutuality, respect, perspective taking, and child development, and, when compared to nonviolent men, they reported using more tactics to undermine coparenting. Perceived problems in coparenting relationships with mothers impacted fathers' relationships with their children.…”
Section: Intimate Partner Violence and Coparenting After Separation/d...mentioning
confidence: 99%
See 3 more Smart Citations
“…Small scale studies in Canada and Norway have compared documented IPV perpetrators with non‐perpetrators and found clear differences in abusive men's perceptions of mothers and of the coparenting relationship (Mohaupt & Duckert, 2022; Thompson‐Walsh et al, 2018). For example, Mohaupt and Duckert (2022) found abusive men's descriptions of coparenting lacked reference to mutuality, respect, perspective taking, and child development, and, when compared to nonviolent men, they reported using more tactics to undermine coparenting. Perceived problems in coparenting relationships with mothers impacted fathers' relationships with their children.…”
Section: Intimate Partner Violence and Coparenting After Separation/d...mentioning
confidence: 99%
“…Perceived problems in coparenting relationships with mothers impacted fathers' relationships with their children. This effect is not unique to coparenting relationships with a history of IPV, but, among fathers who have perpetrated IPV, the effect may be associated with more aggressive parenting and less ability to be empathic to children (Mohaupt & Duckert, 2022; Thompson‐Walsh et al, 2018). Studies compared distressed coparenting fathers with and without IPV and found abusive fathers were more likely to disparage mothers as bad parents, blame mothers for poor coparenting relationships, and lack awareness of the impact of their coparenting on children while simultaneously viewing themselves as powerless to improve coparenting relationships.…”
Section: Intimate Partner Violence and Coparenting After Separation/d...mentioning
confidence: 99%
See 2 more Smart Citations